Crosslinking porcine aortic valve by radical polymerization for the preparation of BHVs with improved cytocompatibility, mild immune response, and reduced calcification. (April 2021) - Xu, Liangpeng; Yang, Fan; Ge, Yao; Guo, Gaoyang; Wang, Yunbing
Over one million artificial heart valve transplantations are performed each year due to valvular stenosis or regurgitation. Among them, bioprosthetic heart valves (BHVs) are increasingly being used because of the absence of the need for lifelong anticoagulation. Almost all of the commercial BHVs are treated with Glutaraldehyde (GLUT). As GLUT-treated BHVs are prone to calcification and structural degradation, their durability is greatly reduced with a service life of only 12–15 years. The physiological structure and mechanical properties of the porcine aortic valve (PAV) are closer to that of a human heart valve, so in this study, PAV is used as the model to explore the comprehensive properties of the prepared BHVs by radical polymerization crosslinking method. We found that PAV treated by radical polymerization crosslinking method showed similar ECM stability and biaxial mechanical properties with GLUT-treated PAV. However, radical polymerization crosslinked PAV exhibited better cytocompatibility and endothelialization potential in vitro cell experiment as better anticalcification potential and reduced immune response than GLUT-treated PAV through subcutaneous animal experiments in rats. To conclude, a novel crosslinking method of non-glutaraldehyde fixation of xenogeneic tissues for the preparation of BHVs is expected.